The Company Fortress : Military Engineering and the Dutch East India Company in South Asia, 1638-1795 - Odegard, Erik. (Leiden : Leiden University Press, 2020)
The remains of Dutch East India Company forts are scattered throughout littoral Asia and Africa. But how important were the specific characteristics of European bastion-trace fortifications to Early Modern European expansion? The Company Fortress takes on this question by studying the system of fortifications built and maintained by the Dutch East India Company (VOC) in present-day India and Sri Lanka. It uncovers the stories of the forts and their designers, arguing that many of these engineers were in fact amateurs and their creations contained serious flaws. Subsequent engineers were hamper.
Appendix 1. Some Remarks on Terminology and Illustrations -- Acknowledgements -- Bibliography -- Archival Sources -- Printed Primary Sources -- Literature -- Index -- Maps and Images -- Tables -- Backcover
Includes bibliographical references and index
Online resource; title from digital title page (viewed on July 14, 2022).
JSTOR
Keywords: Nederlandsche Oost-Indische Compagnie -- History; Nederlandsche Oost-Indische Compagnie; Fortification -- India -- History; Fortification -- Sri Lanka -- History; Military engineering -- India -- History; Military engineering -- Sri Lanka -- History; Génie militaire -- Inde -- Histoire; Génie militaire -- Sri Lanka -- Histoire; Asian history; Military history; HISTORY / General; Fortification; Military engineering; India; Sri Lanka; Asian history; Military history; History